Oncology nurses’ communication challenges with patients and families: A qualitative study - Banerjee, Smita C. (Nurse Educ Pract, 2015)
The benefits of effective communication in an oncology setting are multifold and include the overall well-being of patients and health professionals, adherence to treatment regimens, psychological functioning, and improvements in quality of life. Nevertheless, there are substantial barriers and communication challenges reported by oncology nurses. This study was conducted to present a summary of communication challenges faced by oncology nurses. From November 2012 to March 2014, 121 inpatient nurses working in the oncology setting participated in an online pre-training qualitative survey that asked nurses to describe common communication challenges in communicating empathy and discussing death, dying, and end-of-life (EOL) goals of care. The results revealed six themes that describe the challenges in communicating empathically: dialectic tensions, burden of carrying bad news, lack of skills for providing empathy, perceived institutional barriers, challenging situations, and perceived dissimilarities between the nurse and the patient. The results for challenges in discussing death, dying and EOL goals of care revealed five themes: dialectic tensions, discussing specific topics related to EOL, lack of skills for providing empathy, patient/family characteristics, and perceived institutional barriers. This study emphasizes the need for institutions to provide communication skills training to their oncology nurses for navigating through challenging patient interactions.